Poverty and inequality in rural India - Claire Aubron; Hugo Lehoux; Corentin Lucas (EchoGéo, 2015)
Through a study in two taluks in the State of Gujarat, this article looks at agrarian systems and their relationship with rural poverty, an essential component of “India’s spatial divide”. Based on in-depth fieldwork, it confirms the extreme poverty that is rampant in the Indian countryside, in a state that nonetheless shows a high growth rate. It reveals how this poverty can be explained by an unequal distribution of land and water, but also of added value that is rooted in social relations of dependency, which have fundamentally changed very little over the course of the last decades. Non-agricultural activities, however important they may be, do nothing to change these inequalities. In the light of this work, the agricultural development policies targeting a redressal of inequalities in rural areas seem more necessary than ever.